If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2y + 9 = 0 Reorder the terms: 9 + x + -2y = 0 Solving 9 + x + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + x + -9 + -2y = 0 + -9 Reorder the terms: 9 + -9 + x + -2y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + x + -2y = 0 + -9 x + -2y = 0 + -9 Combine like terms: 0 + -9 = -9 x + -2y = -9 Add '2y' to each side of the equation. x + -2y + 2y = -9 + 2y Combine like terms: -2y + 2y = 0 x + 0 = -9 + 2y x = -9 + 2y Simplifying x = -9 + 2y
| X^2+12x=x-24 | | -9=x/4-7 | | 4=z/9.5 | | 2*2-6=a | | 2*2-6=-6 | | (-4)(7)= | | 5=2-y | | 2y+1=0 | | 0=-3-1y | | (-6)(-7)= | | 2x-8-x=-6 | | 0y-1=1 | | 2x=5x-42 | | 6=16-2y | | -1.1x-2.5=-2.7 | | w=(5/6)^3 | | 0=y-2 | | 21/2-11/3*11/4 | | -34+27= | | 36+x=180 | | 25.2t-24.5=300.5 | | 0.6x-3=2.25 | | 5-19= | | graphy-3x=0 | | 2-1y=0 | | 9(-8)= | | 5x-7/18=-7/12 | | 2=-2y-0 | | 3w^(-4/5)=1/2 | | (4x)(3x+5)= | | 6xy=18 | | 36/2+4 |